Development of a simple assay protocol for high-throughput screening of mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, U; Panchanadikar, V; Sarkar, Dhiman (Journal of Biomolecular Screening, 2005)
Mycobacterium tuberculosis glutamine synthetase (GS) is an essential enzyme involved in the pathogenicity of the organism. The screening of a compound library using a robust high-throughput screening (HTS) assay is currently thought to be the most efficient way of getting lead molecules, which are potent inhibitors for this enzyme. The authors have purified the enzyme to a > 90% level from the recombinant Escherichia coli strain YMC21E, and it was used for partial characterization as well as standardization experiments. The results indicated that the K-m of the enzyme for L-glutamine and hydroxylamine were 60 mM and 8.3 mM, respectively. The K-m for ADP, arsenate, and Mn2+, were 2 mu M, 5 mu M, and 25 mu M, respectively. When the components were adjusted according to their K-m values, the activity remained constant for at least 3 h at both 25 degrees C and 37 degrees C. The Z' factor determined in microplate format indicated robustness of the assay. When the signal/noise ratios were determined for different assay volumes, it was observed that the 200-mu l volume was found to be optimum. The DMSO tolerance of the enzyme was checked up to 10%, with minimal inhibition. The IC50 value determined for L-methionine S-sulfoximine on the enzyme activity was 3 mM. Approximately 18,000 small molecules could be screened per day using this protocol by a Beckman Coulter HTS setup.
Keywords: Beckman Coulter; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Development of a simple high-throughput screening protocol based on biosynthetic activity of Mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, Upasana; Sarkar, Dhiman (Journal of Biomolecular Screening, 2006)
A high-throughput screening protocol has been developed for Mycobacterium tuberculosis glutamine synthetase by quantitative estimation of inorganic phosphate. The K., values determined at pH 6.8 are 22 mM for L-glutamic acid, 0.75 mM for NH4Cl, 3.25 mM for MgCl2, and 2.5 mM for adenosine triphosphate. The K-m value for glutamine is affected significantly by the increase in pH of assay buffer. At the saturating level of the substrate, the enzyme activity at pH 6.8 and 25 degrees C is found to be linear up to 3 h. The reduction of enzyme activity is negligible even in presence of 10% DMSO. The Z' factor and signal-to-noise ratio are found to be 0.75 and 6.18, respectively, when the enzyme is used at 62.5 mu g/ml concentration. The IC50 values obtained at pH 6.8 for both L-methionine S-sulfoximine and DL-phosphothriacin are 500 mu M and 30 pM, respectively, which is lowest compared to the values obtained at other pH levels. The Beckman Coulter high-throughput screening platform was found to take 5 h 9 min to complete the screening of 60 plates. For each assay plate, a replica plate is used to normalize the data. Screening of 1164 natural product fractions/extracts and synthetic molecules from an in-house library was able to identify 12 samples as confirmed hits. Altogether, the validation data from screening of a small set of an in-house library coupled with Z' and signal-to-noise values indicate that the protocol is robust for high-throughput screening of a diverse chemical library.
Keywords: Beckman Coulter; biosynthetic activity; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis

Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Syntheses and biological evaluation of new triazole-spirochromone conjugates as inhibitors of mycobacterium tuberculosis - Muthukrishnan, Murugan; Mujahid, Mohammad; Yogeeswari, P.; Sriram, D. (Tetrahedron Letters, 2011)
A series of novel 1,2,3-triazole fused spirochromone conjugates have been synthesized bearing both spirochromone moiety as well as a 1,2,3-triazole moiety. Some of the compounds have exhibited potential activity against Mycobacterium tuberculosis (virulent strain H37Rv). In particular 5e proved to be the most potent derivative exhibiting MIC = 0.78 mu g/mL. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular activity; Click chemistry; Mycobacterium tuberculosis; Spirochromones

Phyllocladane diterpenes from anisomeles heyneana - Kulkarni, Roshan R.; Shurpali, Ketaki; Gawade, Rupesh L.; Sarkar, Dhiman; Puranik, Vedavati G.; Joshi, Swati P. (Journal of Asian Natural Products Research, 2012)
New phyllocladane diterpene, phyllocladan-16 alpha,17-dihydroxy-19-oic acid (1), together with known phyllocladane diterpene, phyllocladan-16 alpha,19-diol (2), cembrane diterpene ovatodiolide (3), sitosteryl-3-O-beta-D-glucoside (4), and verbascoside (5), were isolated from aerial parts of Anisomeles heyneana. The structure of compound 1 was elucidated by 1D and 2D NMR analyses which included HSQC, HMBC, and nuclear overhauser effect spectroscopy (NOESY) experiments as well as X-ray crystallography. This is the first report of phyllocladane diterpenes from genus Anisomeles. Compounds 1, 3, 4, and 5 were evaluated for inhibition of Mycobacterium tuberculosis and 3 was found to exhibit anti-mycobacterial activity with IC90 6.53 mu g/ml. Compounds 1, 3, and 5, at 100 mu g/ml, were also evaluated for inhibition of Thp-1 cell lines, and compounds 1 and 3 showed 59.02% and 96.4% inhibitions, respectively.
Keywords: Anisomeles heyneana; Lamiaceae; Mycobacterium tuberculosis; phyllocladane diterpenes

Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones

Design and synthesis of a focused library of diamino triazines as potential mycobacterium tuberculosis DHFR inhibitors - Lele, Arundhati C.; Raju, Archana; Khambete, Mihir P.; Ray, M. K.; Rajan, M. G. R.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Degani, Mariam S. (ACS Medicinal Chemistry Letters, 2015)
We report design of a series of 2,4-diamino triazines as Mycobacterium tuberculosis (Mtb) dihydrofolate reductase inhibitors. The synthesized compounds were evaluated against Mtb (H(37)Rv and Dormant stage H37Ra), their cytotoxicity was assessed (HepG2 and A549 cell lines), and selectivity toward Mtb was evaluated by testing against other bacterial strains. Some derivatives showed promising activity along with low cytotoxicity. The most potent compound in the whole cell assay (MIC 0.325 mu M against H(37)Rv) showed selectivity in the enzyme assay and exhibited synergy with second line anti-TB agent p-amino salicylic acid. This study therefore provides promising molecules for further development as antituberculosis DHFR inhibitors.
Keywords: Diamino triazine; dihydrofolate reductase; enzyme assay; molecular modeling; Mycobacterium tuberculosis; selectivity; synergy

Discovery of rimonabant and its potential analogues as anti-TB drug candidates - Gajbhiye, J. M.; More, Namita A.; Patil, Manoj D.; Ummanni, R.; Kotapalli, S. S.; Yogeeswari, P.; Sriram, D.; Masand, Vijay H. (Medicinal Chemistry Research, 2015)
Rimonabant and its analogues have been synthesized in moderate to good yields using a simple synthetic route. All the newly synthesized compounds were subjected to in vitro screening against M. tuberculosis and M. smegmatis. The most potent analogue JMG-14 exhibits MIC value of 3.13 compared to 3.25 and 50 A mu g/ml for ethambutol and pyrazinamide, respectively. The molecular docking reveals that pyrazole ring, number and position of halogen atoms play a crucial role in deciding interactions with MTCYP-121. These findings open up a new avenue in the search of potent anti-TB drugs with rimonabant and its novel analogue JMG-14 as lead molecules.
Keywords: Diaryl pyrazoles; H37Rv; MTCYP-121; Mycobacterium tuberculosis; Rimonabant; tuberculosis

Pharmacophore and docking based virtual screening of validated mycobacterium tuberculosis targets - Vyas, Renu; Karthikeyan, Muthukumarasamy; Nainaru, Ganesh; Muthukrishnan, Murugan (Combinatorial Chemistry & High Throughput Screening, 2015)
Target based virtual screening has surpassed ligand based virtual screening methods in the recent past mainly as it provides more clues regarding intermolecular interactions and takes into consideration the flexible receptor as well. The current methodology describes a computational strategy of predicting Mycobacterium tuberculosis (M. tuberculosis) binders for five well studied targets representing M. tuberculosis proteome encompassing most of the known mechanisms of action. The diversity of the targets was affirmed by their active site analysis and structural studies. The current approach employed pharmacophore searching, docking and clustering techniques in tandem and was validated by enrichment studies using the available Schrodinger data set consisting of 1000 decoys. The application of this methodology was demonstrated by predicting potential molecular targets for fifty newly synthesized compounds. Cross docking studies on the targets were carried out with 4512 known inhibitors utilizing a high performance computing platform to reveal underlying affinity and promiscuity patterns. Optimum binding energy range for all targets as determined by high throughput docking was found to be -3 to -13 kcal/mol.
Keywords: Binding energy; docking; Mycobacterium tuberculosis; open source drug discovery (OSDD); pharmacophore; structure based drug design (SBDD)

Pharmacophore modeling of pretomanid (PA-824) derivatives for antitubercular potency against replicating and non-replicating Mycobacterium tuberculosis - Aher, Rahul Balasaheb; Sarkar, Dhiman (Journal of Biomolecular Structure & Dynamics, 2021)
Pretomanid (PA-824) is the recently (2019) approved drug for the treatment of extensively drug-resistant (XDR) TB and the multidrug-resistant (MDR) TB by US FDA. The experimental data of antitubercular activity of 543 pretomanid derivatives (total 6 datasets) against replicating (active) and non-replicating (dormant) forms of Mycobacterium tuberculosis (strain H37Rv) are available in the literature. Such vast experimental data of pretomanid derivatives against both of these endpoints, and recent approval of pretomanid molecule as a drug encouraged us to utilize this existing experimental information for the development of the 3D-pharmacophore models. The developed model (Hypo-1, MABA) showed the three physicochemical features namely, the oxygen atom of nitro group (HBA_1), fused pyran ring of imidazopyran heterocycle (HYAl_2) and the 4-fluorophenyl moiety (HYAr_3) are crucial for the antitubercular activity against replicating M. tb. Subsequently, the pharmacophore model (Hypo-1, LORA) developed against the non-replicating form of M. tb also showed the contribution of three physicochemical features namely, the 4-tri-fluoromethyl group (HYAl_2) and both the phenyl groups (HYAr_3, HYAr_4) of biaryl moiety in increasing the antitubercular activity. Both the pharmacophoric classifier models showed the classification accuracies of 82.98 and 74.42% for the training set compounds, and 63.91 and 61.60% for the test set compounds respectively, for labelling the compounds into higher and lower active classes. Both the models were also found to be retaining the higher active compounds in top 1.00% of the total number of compounds (decoys and actives), after performing the decoy set screening. Communicated by Ramaswamy H. Sarma
Keywords: LORA assay; MABA assay; Mycobacterium tuberculosis; non-replicating M; pharmacophore modeling; pretomanid derivatives; replicating M; tuberculosis; virtual screening

Synthesis of new 2-(thiazol-4-yl)thiazolidin-4-one derivatives as potential anti-mycobacterial agents - Abhale, Yogita K.; Shinde, Abhijit; Shelke, Monika; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic Chemistry, 2021)
To search for potent antimycobacterial lead compounds, a new series of 3-substituted phenyl-2-(2-(substituted phenyl)thiazol-4-yl) thiazolidin-4-one (5a-t) derivatives have been synthesized by the condensation of 2 substituted phenyl thiazole-4-carbaldehyde with aromatic amine followed by cyclocondensation with thioglycolic acid. The structure of the newly synthesized 2-(thiazol-4-yl)thiazolidin-4-one derivatives were characterized by the spectroscopic analysis. The synthesized compounds were screened for antimycobacterial activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Most of the 2-(thiazol-4-yl)thiazolidin-4-one derivatives showed good to excellent antimycobacterial activity against both the Mtb strains. Nine derivatives 5c, 5g, 5j, 5m, 5n, 5o, 5p, 5s, and 5t showed excellent activity against M. bovis BCG with MIC 4.43 to 24.04 mu M were further evaluated for the cytotoxicity activity against HeLa A549, and HCT-116 cell lines and showed no significant cytotoxic activity at the maximum concentration evaluated. The potential antimycobacterial activities enforced that the thiazolyl-thiazolidin-4-one derivatives could lead to compounds that could treat tuberculosis.
Keywords: Cytotoxicity; Mycobacterium tuberculosis; Thiazole; Thiazolidin-4-one

Detection of a target protein (GroEl2) in Mycobacterium tuberculosis using a derivative of 1,2,4-triazolethiols - Sarkar, Sampa; Swami, Sagar; Soni, Sarvesh Kumar; Holien, Jessica K.; Khan, Arshad; Korwar, Arvind M.; Likhite, Anjali P.; Joshi, Ramesh A.; Joshi, Rohini R.; Sarkar, Dhiman (Molecular Diversity, 2022)
Herein, we identified a potent lead compound RRA2, within a series of 54 derivatives of 1,2,4-triazolethiols (exhibit good potency as an anti-mycobacterial agents) against intracellular Mycobacterium tuberculosis (Mtb). Compound RRA2 showed significant mycobactericidal activity against active stage Mycobacterium bovis BCG and Mtb with minimum inhibitory concentration (MIC) values of 2.3 and 2.0 mu g/mL, respectively. At MIC value, RRA2 compound yielded 0.82 log reduction of colony-forming unit (cfu) against non-replicating Mtb. Furthermore, RRA2 compound was selected for further target identification due to the presence of alkyne group, showing higher selectivity index (> 66.66 +/- 0.22, in non-replicating stage). Using ``click'' chemistry, we synthesized the biotin linker-RRA2 conjugate, purified with HPLC method and confirmed the conjugation of biotin linker-RRA2 complex by HR-MS analysis. Furthermore, we successfully pulled down and identified a specific target protein GroEl2, from Mtb whole-cell extract. Furthermore, computational molecular modeling indicated RRA2 could interact with GroEl2, which explains the structure-activity relationship observed in this study.
Keywords: 1; 2; 4-triazolethiols; GroEl2; Mycobactericidal activity; Mycobacterium bovis BCG; Mycobacterium tuberculosis

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Design, synthesis, anti-mycobacterial activity, molecular docking and ADME analysis of spiroquinoxaline-1,2,4-oxadiazoles via [3+2] cycloaddition reaction under ultrasound irradiation - Kanchrana, Madhu; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (MOLECULAR DIVERSITY, 2024)
Keywords: 2; 4-oxadiazoles; cytotoxicity activity; molecular; Mycobacterium tuberculosis; Spiroquinoxaline-1